Hassan Gardezi & Jamil Rashid (Eds.), Pakistan: The Roots of Dictatorship. The Political Economy of a Praetorian State, London: Zed Press, 1983, 412 s., 8 £; Kirsten Westergaard, State and Rural Society in Bangladesh. A study in relationship, London and M - Larsen, Arne (Politica, 1986)
Hassan Gardezi & Jamil Rashid (Eds.), Pakistan: The Roots of Dictatorship. The Political Economy of a Praetorian State, London: Zed Press, 1983, 412 s., 8 £; Kirsten Westergaard, State and Rural Society in Bangladesh. A study in relationship, London and Malmo: Curzon Press, 1985, 198 s., 6.50 £.